Prevalence of exclusive breastfeeding and associated factors among mothers in rural Bangladesh: a cross-sectional study - Joshi, Prakash Chandra; Angdembe, Mirak Raj; Das, Sumon Kumar; Ahmed, Shahnawaz; Faruque, Abu Syed Golam; Ahmed, Tahmeed (© 2014 BioMed Central Ltd., 2017)
This article was published in International Breastfeeding Journal [© 2014 BioMed Central Ltd.] and the definite version is available at: https://internationalbreastfeedingjournal.biomedcentral.com/articles/10.1186/1746-4358-9-7